Beavers and Other Rodents - Goldish, Meish; World Book, Inc. (Chicago : World Book, 2002)
Provides information about the physical characteristics, habits, and behavior of beavers and such related rodents as flying squirrels, pocket gophers, mice, and lemmings.
Includes ibibliographical references (p. 64) and index.
Keywords: Beavers -- Juvenile literature; Rodents -- Juvenile literature